The Impact of Openness to diversity to Work Motivation: Case Study in Banking Industry in Greater Jakarta, Indonesia - Mentari de Tanzil (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2019)
The objectives of this research are to find out how the employee openness to diversity is in banking industry; and what is impact of employee openness to diversity to work motivation. The research was perfomed using quantitave method and the data obtained by administering questionnaire to 200 bank employee in Greater Jakarta area. The result revealed that openness to diversity has positive impact to work motivation. There are three dimensions of openness to diversity , including openness to gender differences, openness to religion differences, and openness to ethnic differences. All the three dimensions have positive and significant impact to work motivation. It means, when the three dimensions are enhanced, the work motivation will increase. However, among the three dimensions, openness to gender differences has the most significant influence to work motivation. Followed by openness to religion differences and the openness to ethnic differences.